Empowering SME Entrepreneurs: Exploring E-Mind and Financial Self-Efficacy - Yusnita*, Maya; Wardhani, Rulyanti Susi; Yunita, Anggraeni (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This study aims to analyze the readiness of SME entrepreneurs in Pangkal Pinang for digital entrepreneurship acceleration and global expansion, taking into consideration the perspectives of Entrepreneurial Mindset (E-Mind) and Financial Self-Efficacy. Data collection was conducted through surveys with in-depth interviews and questionnaires administered to SME entrepreneurs in Pangkal Pinang. Data analysis used a quantitative descriptive approach with IBM SPSS software. The research findings reveal that SME entrepreneurs in Pangkal Pinang possess a strong Entrepreneurial Mindset (E-Mind), as evidenced by their consistent initiative-taking and responsibility for their actions. They are also adept at recognizing and capitalizing on opportunities for business development. The study further highlights the favorable Financial Self-Efficacy among SME entrepreneurs in Pangkal Pinang, characterized by their confidence in financial management and belief in their ability to achieve financial goals in business management.Keywords: E-Mind; Financial Self-Efficacy; Digital Marketing; Financial Technology; Digital Leadership